Infantile Cellular Schwannoma Developing on the Skin with Atypical Clinical Features - Taku Fujimura; Hachiro Tagami; Setsuya Aiba (Karger Publishers, 2014)
Cellular schwannoma (CS) is a variety of schwannoma with a predominantly cellular growth, normally developing in middle-aged patients. In this report, we describe a 15-month-old infant with primary cutaneous CS on the knee. Because of its histologically malignant features, CS is sometimes overdiagnosed as a malignant nerve tumor. Therefore, awareness of this variant of schwannoma is important for dermatologists to avoid needless treatments for patients with CS.